2014
DOI: 10.3389/fmicb.2014.00217
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic alternatives: the substitution of antibiotics in animal husbandry?

Abstract: It is a common practice for decades to use of sub-therapeutic dose of antibiotics in food-animal feeds to prevent animals from diseases and to improve production performance in modern animal husbandry. In the meantime, concerns over the increasing emergence of antibiotic-resistant bacteria due to the unreasonable use of antibiotics and an appearance of less novelty antibiotics have prompted efforts to develop so-called alternatives to antibiotics. Whether or not the alternatives could really replace antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
352
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(366 citation statements)
references
References 171 publications
(204 reference statements)
2
352
1
11
Order By: Relevance
“…Substantial evidence indicated that plant bioactives have positive implications on gut health and productive performance of poultry, and are generally recognized as safe (Yang et al, 2015;Franz et al, 2010). Nevertheless, the use of phytogenic compounds as animal feed additives may include potential side effects such as toxicity (Lambert et al, 2001;Cheng et al, 2014). Hence, as stated by Yang et al, (2015), a complete assessment of the toxicity and safety of phytogenic compounds is needed before the compounds can be used extensively in animal feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicated that plant bioactives have positive implications on gut health and productive performance of poultry, and are generally recognized as safe (Yang et al, 2015;Franz et al, 2010). Nevertheless, the use of phytogenic compounds as animal feed additives may include potential side effects such as toxicity (Lambert et al, 2001;Cheng et al, 2014). Hence, as stated by Yang et al, (2015), a complete assessment of the toxicity and safety of phytogenic compounds is needed before the compounds can be used extensively in animal feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics seem to be one of the most promising group of substances that may exert such properties (Cheng et al, 2014). Prebiotics are defined as a 'non-digestible food ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon, thus improving host health'.…”
Section: Introductionmentioning
confidence: 99%
“…Effective substances of garden thyme also affect the antibiotic-resistant microbes [23][24][25][26]; in certain cases, they might replace antibiotics [27][28][29] and might present sound alternative to growth promoters [4,30]. These joint effects improve food safety and sustainability of animal agriculture.…”
Section: Discussionmentioning
confidence: 99%